Assessment of post-menopausal osteoporosis development risk: role of polymorphisms RS1800012, RS1107946 of a gene of COL1A1 and RS731236 and RS11568820 of a gene of VDR - D. S. Zyablicev; A. S. Larin (Journal of Education, Health and Sport, 2015)
Zyablicev D. S., Larin A. S. Оцінка ризику розвитку постменопаузного остеопорозу: роль поліморфізмів rs1800012 і rs1107946 гена COL1A1 та rs731236 і rs11568820 гена VDR = Assessment of post-menopausal osteoporosis development risk: role of polymorphisms rs1800012, rs1107946 of a gene of COL1A1 and rs731236 and rs11568820 of a gene of VDR. Journal of Education, Health and Sport. 2015;5(2):333-340. ISSN 2391-8306. DOI 10.5281/zenodo.18861